1997
DOI: 10.1046/j.1365-2036.1997.00223.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐course therapy with amoxycillin–clarithromycin triple therapy for 10 days (ACT‐10) eradicates Helicobacter pylori and heals duodenal ulcer

Abstract: Background: Whilst the role of Helicobacter pylori eradication in managing duodenal ulcers has been established, consensus regarding the ideal regimen has not been achieved. Methods: Patients with H. pylori‐positive active duodenal ulcer were randomly assigned to receive triple therapy with amoxycillin 1000 mg b.d. + clarithromycin 500 mg b.d. + omeprazole 20 mg daily for 10 days (ACT‐10) or dual therapy with clarithromycin 500 mg t.d.s. + omeprazole 40 mg daily for 14 days (Dual). No additional acid suppressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 19 publications
7
53
0
Order By: Relevance
“…31,32 As expected based on the results of others, 33 we found the H pylori eradication rate of a clarithromycin-containing triple therapy regimen is compromised in patients infected with a clarithromycinresistant organism: H pylori eradication in 94% of patients infected with clarithromycin-susceptible strains and 47% of patients with clarithromycin-resistant strains. Our results are also consistent with those of Wurzer et al 34 and Schwartz et al, 29 who suggested that secondary clarithromycin resistance develops infrequently among patients treated with a proton pump inhibitor combined with clarithromycin and another antibiotic.…”
Section: Compliance and Adverse Effectssupporting
confidence: 82%
“…31,32 As expected based on the results of others, 33 we found the H pylori eradication rate of a clarithromycin-containing triple therapy regimen is compromised in patients infected with a clarithromycinresistant organism: H pylori eradication in 94% of patients infected with clarithromycin-susceptible strains and 47% of patients with clarithromycin-resistant strains. Our results are also consistent with those of Wurzer et al 34 and Schwartz et al, 29 who suggested that secondary clarithromycin resistance develops infrequently among patients treated with a proton pump inhibitor combined with clarithromycin and another antibiotic.…”
Section: Compliance and Adverse Effectssupporting
confidence: 82%
“…Factors contributing to eradication include reduced compliance to medication schedules, genetic polymorphisms of drug-metabolizing enzymes, and increased resistance to antimicrobial agents (2,7,26). It was previously reported that resistance to CLR among H. pylori isolates in Japan has been increasing (1,9,11,14,27). It can be speculated that inadequate empirical treatment due to a lack of current antimicrobial susceptibility data is exacerbating the problem of increasing resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the relative clinical effectiveness of low-dose longterm therapy with macrolides in the treatment of chronic respiratory infections may account for the failure of H. pylori eradication in those patients. The high failure rate observed when CLR is employed in an eradication regimen in the presence of CLR-resistant strains as well as the association of eradication failure and CLR resistance have been reported (9,27). The not-uncommon occurrence of suboptimal eradication therapy would predict a further increase in the incidence of CLR-resistant H. pylori strains.…”
Section: Discussionmentioning
confidence: 99%
“…Most of those studies were conducted with a 10-14-day regimen, 3,4,6,8 or with a colloidal bismuth subcitrate. 11 However, one study using a 1-week triple therapy, without prolongation of the anti-secretory drug, has shown that approximately 80% of H. pylori-associated duodenal ulcers were healed after 28 days.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have suggested that treatment for eradication of H. pylori without prolongation of anti-secretory treatment is sufficient to heal most of the duodenal ulcer. [1][2][3][4][5][6][7][8][9] The present study tests the hypothesis that the 1-week triple therapy for eradication of H. pylori alone is a convenient therapy regimen for uncomplicated H. pylori-associated duodenal ulcer.…”
Section: Introductionmentioning
confidence: 99%